PERENCANAAN BETON FILTER UNTUK FILTER AIR - Trias Melati Mael (Gorontalo Journal of Infrastructure and Science Engineering, 2021)
non-gravel concrete filters are very effective in reducing the turbidity of water because of sands filters which can hold the suspended particles in order to produce clean water whin can be used. The non-gravel concrete filter design is used trial and error method in doing mix design with ensuring testing of the characteristics of concrete mix materials following SNI. In order to maximize the non-gravel concrete filters performance, the fine aggregate must have sludge levels (L) less that 0.5% (L> 0.5%) and ensure that the surface inside the pipe as a print media is rough in preventing non-gravel concrete filters do not easily slip or fall from mold due to water pressure. Three variants of concrete filters are distinguished based on sand - cement ratio 1: 5 (T-1), 1: 7 (T-2), and 1: 9 (T-3), in the form of volume comparison by having each - five different samples. Based on the quality standard of turbidity of water is established by the Ministry of Health of Indonesia as a reference is 25 NTU. The findings reveal that the first variant of T-1 has turbidity of water average 1.62 NTU with water discharge 58.4 second / l, second variant has turbidity of water average 12.18 NTU with water discharge 55.8 second / l, and third has turbidity of water average 18,61 NTU with water discharge 13,8 second /. It can be seen that all variants produce a useful turbidity of water based on quality standards of the Indonesian Ministry of Health. The optimal performance of concrete filters results can conclude that the relation between the quality of turbidity of water is inversely proportional to the generated water discharge, so that the third variant concrete (t-3 can be categorized as concrete that can work optimally.Beton filter non kerikil sangat efektif dalam mereduksi kekeruhan air dikarenakan filter pasir yang mampu menahan partikel tersuspensi agar dapat menghasilkan air bersih yang layak digunakan. mendesain beton filter  menggunakan metode trial and eror dalam melakukan mix design dengan memastikan pengujian karateristik bahan campuran beton mengikuti SNI. Agar memaksimalkan kinerja beton filter, Agregat halus harus memiliki kadar lumpur  (L) kurang dari 0,5% (L > 0,5%) dan pastikan permukaaan dalam pipa sebagai media cetak dalam keadaan kasar hal ini mencegah agar beton filter tidak mudah slip  atau jatuh dari cetakan karena tekanan air. Tiga varian beton filter dibedakan berdasarkan rasio pasir – semen 1:5(T-1), 1:7(T-2), dan 1:9(T-3), dalam bentuk perbandingan volume dengan memilii masing-masing lima sampel berbeda. Berdasarkan standar mutu kekeruhan air yang ditetapkan Menteri Kesahatan Republik Indonesia sebagai acuan adalah 25 NTU. Hasil yang didapatkan varian pertama T-1 memiliki rata-rata mutu kekeruhan air sebesar 1,61 NTU dengan debit air 58,4 dtk/l, varian kedua memiliki rata-rata mutu kekeruhan air sebesar 12,18 NTU dengan debit air yang dihasilkan 55,8 dtk/l dan varian ketiga memiliki rata-rata mutu kekeruhan air sebesar 18,61 NTU dengan debit air yang dihasilkan 13,8 NTU. Hasil diatas menunjukan bahwa semua varian menghasilkan mutu kekeruhan air yang layak digunakan berdasarkan standar mutu kekeruhan air yang ditetapkan Menteri Kesahatan Republik Indonesia. Hasil kinarja yang oplimal beton filter dapat disimpulkan berdasarkan hubungan antara mutu kekeruhan air yang berbanding terbalik dengan  debit air yang dihasilkan sehingga beton varian ketiga T-3 dapat dikategorian sebagai beton yang dapat bekerja secara optimum